ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN USAHA PRODUKSI TEH HERBAL ALAMI DAUN KELOR (Moringa oleifera) CV. ATLANTIC, ACEH UTARA - Yani, Risma; Mastuti, Rini; Gustiana, Cut (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The aim of this study was to identify the important factors that influence the development of a natural herbal tea production business from Moringa oleifera leaves in Tanjung Ara Village, Tanah Jambo Aye District, North Aceh District. This study uses the case study method, with a focus on SWOT analysis, to find different business development strategies. Five key respondents were selected to provide input on internal and external strategic factors that influence business development. According to the results of the study, the alternative SO strategy obtained the highest score and was suggested as the best strategy that is feasible to apply in the development of natural herbal tea production of Moringa leaves.